Aplikasi pestisida dan analisis residunya pada produksi beras petani di kampung sidomulyo distrik oransbari kabupaten manokwari selatan - Saraswati Prabawardani; Gunawan Gunawan; Wasgito Purnomo (Cassowary, 2020)
Rice is a source of staple food whose fulfillment is a basic human right in realizing quality human resources. Therefore, in order to meet food needs, the Indonesian government has conducted various programs to increase production of various food commodities. One of the most important is the increase in national rice production through an intensification and intensification program. Control of plant pests (OPT) is a problem that is often faced by farmers. The use of synthetic pesticides is the easiest step for farmers to take. The use of pesticides in South Manokwari Regency is very high, this can be seen from the presence of kiosks that sell synthetic pesticides with a variety of trademarks, active ingredients and formulators in every agricultural center in the area of ​​South Manokwari Regency. There are 1 distributor and 12 retailers and 148 types of pesticides that have been circulating in the area of ​​South Manokwari Regency. The purpose of this study was to determine the Application of Pesticides and Residue Analysis in Farmer Rice Production in Sidomulyo Village, Oransbari District, South Manokwari District. This research is descriptive with survey techniques, direct interviews to obtain an overview of the application procedures, types, dosages, and frequency of use of pesticides and analyze the accumulation of pesticides in rice. The types of pesticides most widely used by farmers in Sidomulyo village in their efforts to control Plant Pests (OMO) in lowland rice cultivation are Demolish, Resotin and Klensect. The application is carried out by farmers by spraying so that there is direct contact between the control material, the control target and the plants. The dosage used by farmers in control is 300-340 liters / ha with the frequency of spraying 6-7 times each season. The results of the analysis of pesticide residues on rice products from Sidomulyo village farmers show that the residue is below the maximum residue limit set so that the rice produced by these farmers is safe for consumption. The research analysis shows that there is no correlation between the pesticide residues in rice produced by farmers in Sidomulyo village and the types of pesticides used, the frequency of application, the dosage / concentration of pesticides and the application method used by farmers.